Prevalence of mental health issues among adolescents - Vijaykumar, Kavya; Hirevenkanagoudar, Usha; Chetty , Sanjeev (International Journal of Contemporary Pediatrics, 2024)
Background: Adolescents constitute a major group of population in India. Mental health problems are not so uncommon among them. Since there is lack of awareness concerning the seriousness of mental ill health and it’s adverse effects on growing population it is essential to have an estimate of percentage of adolescent population effected. Methods: It is a cross-sectional study conducted in a school on 330 students studying in 9th to 12th std in Raichur district. Mental health was assessed by questionnaire called Warwick Edinburg mental wellness score. Results: Overall, 14.2% of adolescents had poor mental health scores which was more among girls in comparison to boys. Conclusions: The prevalence of mental health issues among adolescents is rising concern that requires proper attention and action by health care providers, educators, and parents of the child. Early intervention is essential to ensure the well-being of young people.